Abnormal coagulation parameters are associated with poor prognosis in patients with novel coronavirus pneumonia - Tang, Ning; Li, Dengju; Wang, Xiong; Sun, Ziyong (Journal of thrombosis and haemostasis, 2020)
Background In the recent outbreak of novel coronavirus infection in Wuhan, China, significantly abnormal coagulation parameters in severe novel coronavirus pneumonia (NCP) cases were a concern. Objectives To describe the coagulation feature of patients with NCP. Methods Conventional coagulation results and outcomes of 183 consecutive patients with confirmed NCP in Tongji hospital were retrospectively analyzed. Results The overall mortality was 11.5%, the non‐survivors revealed significantly higher D‐dimer and fibrin degradation product (FDP) levels, longer prothrombin time and activated partial thromboplastin time compared to survivors on admission (P < .05); 71.4% of non‐survivors and 0.6% survivors met the criteria of disseminated intravascular coagulation during their hospital stay. Conclusions The present study shows that abnormal coagulation results, especially markedly elevated D‐dimer and FDP are common in deaths with NCP.